Effect of Deuterated Aspirin Treatment of Obese Iraqi Patients With Blood Hyperviscosity Syndrome - Al-Kinany, Sura Q; Одсек за хемију, Природно-математички факултет, Универзитет Мустансирија, Багдад, Ирак., Одсек за хемију, Природно-математички факултет, Универзитет Мустансирија, Багдад, Ирак.; Dr; AM Al Taie , Wasan (Scripta Medica, 2026)
Background/Aim: Hyperviscosity syndrome (HVS) is a predictor of blood flow resistance and blood viscosity, density, or thickness. A number of factors that influence blood viscosity have been identified. This study aimed to compare the effects of the deuterated aspirin (aspirin-D) to standard aspirin (aspirin-H) on the prothrombin time (PT) and the normalised international ratio (INR) in obese HVS patients and healthy individuals of normal weight. Haematocrit (HCT) was the primary determinant of blood viscosity and flow resistance. Methods: The study included 120 Iraqi individuals, aged between 21 and 55 years, divided into 2 groups, 60 patients in an obese HVS group and 60 in a healthy weight control group. Total complete blood count, haemoglobin (Hb), the effects of aspirin-H and aspirin-D on blood viscosity were evaluated by measuring HCT, red blood cell (RBC), PT and INR. Results: Patients aged 31–41 years with a body mass index (BMI) of 30–39.9 kg/m² constituted the largest proportion of the HVS group (41.66 %), while the same age group represented the highest percentage among healthy controls (40 %). Patients with HVS showed highly significant increases (p < 0.001) in anthropometric and haematological parameters, including BMI, Hb, HCT and RBC, along with a significant reduction in PT and INR compared to controls. Aspirin treatment, particularly deuterated aspirin, significantly increased PT and INR values, indicating improved anticoagulant activity. Conclusion: Aspirin-D was superior to standard aspirin-H in reducing blood viscosity and delaying clotting time in both HVS patients and healthy subjects.